Tree dimension and environmental correlates of heartwood content in Siamese rosewood (Dalbergia cochinchinensis) - Ponthep Meunpong; Chatcharin Penboon; Nawaphong Kuasakun; Chongrak Wachrinrat (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Meunpong P, Penboon C, Kuasakun N, Wachrinrat C. 2021. Tree dimension and environmental correlates of heartwood content in Siamese rosewood (Dalbergia cochinchinensis). Biodiversitas 22: 3297-3303. Siamese rosewood (Dalbergia cochinchinensis) is considered amongst the prime timber varieties in high demand with the wood fetching high prices in the international timber market. Therefore, illegal logging and smuggling of Siamese rosewood from natural forests poses a severe problem in Thailand. Heartwood and its content is the most valuable part of Siamese rosewood, which in practice, cannot be measured directly in living trees. Hence, we investigated the relationship between the heartwood content of Siamese rosewood, and tree dimension and environmental characteristics across eleven plantations throughout Thailand construct a model for predicting the heartwood content using specific environmental variables. The results indicate that there were differences in the mean annual increment of all measurement parameters (d0, d30, dbh, and total height of a tree) across eleven plantations studied. However, we did not find any statistically significant differences between the increments in heartwood diameter. Furthermore, we found that suitable location for Siamese rosewood plantation could result in doubling of growth rate. We report that dbh was the most relevant variable and could be used as a predictor for heartwood content. In terms of environmental variables, soil properties at top layer that affect the heartwood content were particle density, organic matter, and silt particles. Using the resulted equation formulated in this study may be useful when planning areas for suitable plantations of Siamese rosewood in Thailand.